Customary Law As An Aspect Of Legal PluralisM: With Particular Reference To British Colonial Africa - Marasinghe, Lakshman (Journal of Malaysian and Comparative Law, 2019)
Legal pluralism denotes the interaction of two or more systems of laws within a separate legal unit. The study of legal pluralism is undertaken today as an aspect of the impact of colonialism upon Developing Nations of the Third World. The departing colonial powers had left behind in their former Colonies and Dependencies.